Accurately Determining Labor Test Results Using the Rough Set Method - Retno Devita; Sarjon Defit (Postgraduate, University of Mataram, 2024)
An exam is something that must be done to test a person's ability or intelligence. The laboratory exam in the Computer Systems study program at Putra Indonesia University